(untitled) (Archives of Pediatrics of Uruguay, 2026)
Introduction: galactorrhea in adolescents is a rare clinical finding with variable etiology, ranging from physiological to pathological conditions. Its diagnostic approach must be systematic and individualized to determine the need for treatment. Objectives: to describe a comprehensive clinical-diagnostic approach for the evaluation of adolescents with galactorrhea, highlighting the most frequent causes, recommended tests, and therapeutic strategies. Methodology: a narrative review was conducted based on clinical guidelines and updated scientific literature on galactorrhea in the adolescent population, including national and international sources. We propose a stepped study algorithm guided by the clinical presentation. Conclusions: in post-pubertal adolescents, pregnancy must be ruled out as the primary cause. Medications, especially antipsychotics, represent the most common secondary cause. Other frequent etiologies include hypothyroidism, polycystic ovary syndrome, and, less frequently, prolactinomas. In most cases, specific treatment is not necessary, except when there is persistent hyperprolactinemia, associated symptoms, or a treatable organic cause.